Positive electrode material and secondary battery
By using the positive electrode material with a core-shell structure in lithium-ion batteries, and using the MOFs-derived carbon composite material of LiMnYFeXAZPO4 as the core layer and the metal B-doped COFs-derived carbon as the shell layer, the problem of insufficient performance of the positive electrode material in the prior art is solved, and higher battery capacity and better cycle and rate performance are achieved.
Patent Information
- Application Number
- CN202411990317.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
When lithium manganese iron phosphate (LMFP) is used as the positive electrode material in existing lithium-ion batteries, there are problems such as low capacity, poor circulation and rate performance, and it is easy to cause the dissolution of manganese metal, affecting the safety performance and service life of the battery.
A positive electrode material adopts a core-shell structure, wherein the core layer is a MOFs-derived carbon composite of LiMnYFeXAZPO4, and the shell layer is metal B-doped COFs-derived carbon, and defines the molar ratio range of the core layer and the shell layer. The structure is synthesized by hydrothermal reactions to form an efficient conductance path and stabilize the cathode material.
It effectively reduces the Jaha-Teller effect of lithium manganese iron phosphate during the circulation process, inhibits the dissolution of manganese, improves the conductivity and stability of the positive electrode material, and thus improves the capacity, rate performance and cycle performance of the secondary battery.
Smart Images

Figure BDA0005223503860000111 
Figure BDA0005223503860000121 
Figure BDA0005223503860000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, in particular to a positive electrode material and a secondary battery. Background Art
[0002] In lithium-ion batteries, lithium manganese iron phosphate (LMFP) with an olivine structure has the problem of low electronic conductivity and ionic conductivity, and as the lithium-ion battery is charged and discharged, lithium ions will continue to be deintercalated and intercalated, causing the Jaha-Teller effect. The Jaha-Teller effect can cause changes in the structure of the positive electrode material, and even seriously affect the crystal form of the positive electrode material, causing it to be deformed and the electrochemical performance to decrease. As the lithium-ion battery is charged and discharged, lithium manganese iron phosphate (LMFP) is also prone to interfacial side reactions, resulting in the dissolution of the metal element manganese. The above problems lead to poor rate performance and poor low-temperature performance of lithium manganese iron phosphate (LMFP), which in turn affects the safety performance of lithium-ion batteries and damages the service life of lithium-ion batteries. Summary of the invention
[0003] The purpose of the present application is to solve the problem in the prior art that when lithium manganese iron phosphate is used as the positive electrode material, the secondary battery obtained has low capacity, poor cycle performance and poor rate performance, and to propose a positive electrode material and a secondary battery.
[0004] To achieve the above object, the first aspect of the present application provides a positive electrode material, wherein the positive electrode material is a core-shell structure, and the core layer includes LiMn Y Fe X A Z A MOFs-derived carbon composite material of PO4, wherein the shell layer comprises metal B-doped COFs-derived carbon;
[0005] LiMn Y Fe X A Z In PO4, 0<X<1, 0<Y<1, 0.001≤Z / (X+Y)≤0.005, X+Y+Z=1;
[0006] A is selected from at least one of Ni, Al, Fe, Mg, Cu, Ti, W, La, Zr, Nb, Pd, Co, Ni, Mn, Zn, and Ta;
[0007] In the metal B-doped COFs-derived carbon, the metal B includes at least one of Co, La, Ti, Zr, and Sc;
[0008] The molar ratio of the core layer to the shell layer is 1:(0.001-0.005).
[0009] As an embodiment of the present application, in the metal-doped COFs-derived carbon, the number of carbon-carbon double bonds in the smallest monomer molecule is ≥ 2, preferably 2 to 6.
[0010] As an embodiment of the present application, the LiMn Y Fe X A Z The number of carbon anchor points of MOFs-derived carbon in MOFs-derived carbon composites of PO4 is similar to that of LiMn Y Fe X A Z The molar mass content ratio of phosphorus element in PO4 is 0.001-0.02.
[0011] In a second aspect of the present application, the present application provides a method for preparing the positive electrode material, the preparation method comprising the following steps:
[0012] (1) mixing the A source, the MOFs organic ligand and water to perform a first hydrothermal reaction to obtain an A-MOFs solution;
[0013] (2) mixing the metal B source, the COFs organic ligand and water to perform a second hydrothermal reaction to obtain a metal B-COFs solution;
[0014] (3) Add the phosphorus source aqueous solution to the lithium source aqueous solution and stir, then add the mixed aqueous solution of the iron source and manganese source and stir, then add the A-MOFs solution and heat to react, cool, filter and wash after the reaction is completed, and obtain LiMn Y Fe X A Z MOFs-derived carbon composite precursors of PO4;
[0015] (4) LiMn Y Fe X A Z The PO4 MOFs-derived carbon composite material precursor and the metal B-COFs are mixed and subjected to a third hydrothermal reaction, and after the reaction is completed, the mixture is cooled, filtered, washed, and dried to obtain a precursor powder;
[0016] (5) Calcine the precursor powder to obtain the positive electrode material.
[0017] As an embodiment of the present application, in the step (1), the temperature of the first hydrothermal reaction is 185-225°C and the time is 22-26h.
[0018] As an embodiment of the present application, in the step (2), the temperature of the second hydrothermal reaction is 185-225°C and the time is 22-26h.
[0019] As an embodiment of the present application, in the step (3), the heating reaction temperature is 190-240°C and the time is 13-17h.
[0020] As an embodiment of the present application, in the step (4), the temperature of the third hydrothermal reaction is 150-210°C and the time is 22-26h.
[0021] As an embodiment of the present application, in the step (5), the calcination temperature is 380-490°C and the calcination time is 9-13h.
[0022] As an embodiment of the present application, the COFs organic ligand includes at least one of terephthalaldehyde and 4',4-(benzothiadiazole-4,7-diyl)-dibenzaldehyde.
[0023] As an embodiment of the present application, the MOFs organic ligand includes at least one of terephthalic acid and isophthalic acid.
[0024] As an embodiment of the present application, based on the mass of metal B-COFs, the mass percentage of metal B is 6-10%.
[0025] As an embodiment of the present application, the A source includes at least one of A oxide, A nitrate, and A hydroxide.
[0026] As an embodiment of the present application, the lithium source includes at least one of lithium hydroxide and lithium carbonate.
[0027] As an embodiment of the present application, the phosphorus source includes at least one of phosphoric acid and sodium phosphate.
[0028] As an embodiment of the present application, the iron source includes at least one of ferrous sulfate and its hydrate, and ferrous acetate.
[0029] As an embodiment of the present application, the manganese source includes at least one of manganese sulfate and its hydrate, and manganese carbonate.
[0030] In the third aspect of the present application, the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode active material layer includes the positive electrode material described in the present application.
[0031] In a fourth aspect of the present application, the present application provides an electrical device, wherein the electrical device comprises the secondary battery described in the present application.
[0032] Compared with the prior art, the beneficial effects of this application are:
[0033] The positive electrode material provided in the present application is a core-shell structure, wherein the core layer includes LiMn Y Fe X A Z The invention relates to a MOFs-derived carbon composite material of PO4, wherein the shell layer includes metal B-doped COFs-derived carbon, and the molar ratio range of the core layer and the shell layer is limited; on the one hand, the obtained positive electrode material can reduce the Jaha-Teller effect of lithium manganese iron phosphate during the cycle and inhibit the dissolution of manganese; on the other hand, both the core layer and the shell layer contain derived carbon, which can effectively improve the conductivity of the positive electrode material; on the other hand, the specific molar ratio range of the core layer and the shell layer can effectively stabilize the positive electrode material; therefore, when the obtained positive electrode material is applied to the preparation of a secondary battery, the obtained secondary battery has excellent capacity, rate performance and cycle performance. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0037] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0038] In one embodiment of the present application, the present application proposes to provide a positive electrode material, wherein the positive electrode material is a core-shell structure, and the core layer includes LiMn Y Fe X A Z A MOFs-derived carbon composite material of PO4, wherein the shell layer comprises metal B-doped COFs-derived carbon;
[0039] LiMn YFe X A Z In PO4, 0<X<1, 0<Y<1, 0.001≤Z / (X+Y)≤0.005, X+Y+Z=1;
[0040] A is selected from at least one of Ni, Al, Fe, Mg, Cu, Ti, W, La, Zr, Nb, Pd, Co, Ni, Mn, Zn, and Ta;
[0041] In the metal B-doped COFs-derived carbon, the metal B includes at least one of Co, La, Ti, Zr, and Sc;
[0042] The molar ratio of the core layer to the shell layer is 1:(0.001-0.005).
[0043] The positive electrode material provided in the present application is a core-shell structure, wherein the core layer includes LiMn Y Fe X A Z The invention relates to a MOFs-derived carbon composite material of PO4, wherein the shell layer includes metal B-doped COFs-derived carbon, and the molar ratio range of the core layer and the shell layer is limited; on the one hand, the obtained positive electrode material can reduce the Jaha-Teller effect of lithium manganese iron phosphate during the cycle and inhibit the dissolution of manganese; on the other hand, both the core layer and the shell layer contain derived carbon, which can effectively improve the conductivity of the positive electrode material; on the other hand, the specific molar ratio range of the core layer and the shell layer can effectively stabilize the positive electrode material; therefore, when the obtained positive electrode material is applied to the preparation of a secondary battery, the obtained secondary battery has excellent capacity, rate performance and cycle performance.
[0044] It should be noted that the types of A and metal B are obtained through ICP (element analysis) testing.
[0045] It should be noted that the molar ratio of the core layer to the shell layer is obtained by transmission electron microscopy (TEM) combined with electron energy loss spectroscopy (EELS) testing.
[0046] It should be noted that LiMn Y Fe X A Z In PO4, the amounts of X, Y, and Z are obtained through ICP testing.
[0047] Exemplarily, the molar ratio of the core layer to the shell layer may be 1:(0.001-0.005), any point value or any range value between two points, such as 0.001, 0.002, 0.003, 0.004, 0.005, etc.
[0048] In one embodiment, in the metal B-doped COFs-derived carbon, the number of carbon-carbon double bonds in the smallest monomer molecule is ≥ 2.
[0049] It should be noted that the number of carbon-carbon double bonds in the smallest monomer molecule of metal-doped COFs-derived carbon is obtained through infrared spectroscopy testing.
[0050] In one embodiment, the metal-doped COFs-derived carbon has 2-6 carbon-carbon double bonds in the smallest monomer molecule.
[0051] This study found that due to LiMn Y Fe X A Z LiMn in MOFs-derived carbon composites of PO4 Y Fe X A Z PO4 is distributed in or on the MOFs-derived carbon lattice, that is, there is metal in the core layer. Therefore, during the preparation stage, the carbon-carbon double bonds on COFs can be chemically bonded to the metal in the core layer to form a self-assembled coating, thereby effectively improving the stability of the positive electrode material, and then improving the comprehensive performance of the secondary battery prepared later. When metal B is further selected to dope COFs-derived carbon, the carbon-carbon double bonds in the smallest monomer molecule are ≥2, especially 2-6, the more anchor links there are and the stronger the coating stability, which makes the secondary battery have a higher capacity, and the cycle performance and rate performance are better.
[0052] In one embodiment, the LiMn Y Fe X A Z The number of carbon anchor points of MOFs-derived carbon in MOFs-derived carbon composites of PO4 is similar to that of LiMn Y Fe X A Z The molar mass content ratio of phosphorus element in PO4 is 0.001-0.02.
[0053] It should be noted that the number of carbon anchor points of MOFs-derived carbon was obtained through infrared spectroscopy testing.
[0054] It should be noted that LiMn Y Fe X A Z The molar mass of phosphorus in PO4 is obtained by ICP testing.
[0055] For example, the number of carbon anchor points of MOFs-derived carbon is similar to that of LiMn Y Fe X A ZThe ratio of the molar mass content of phosphorus element in PO4 can be any point value or any two point range values between 0.001-0.02, for example, it can be 0.001, 0.003, 0.005, 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, 0.02, etc.
[0056] This study found that the number of carbon anchor points of MOFs-derived carbon is similar to that of LiMn Y Fe X A Z When the molar mass content ratio of phosphorus in PO4 is within a certain range, the number of anchor points can be reasonably controlled on the one hand, and the MOFs-derived carbon in LiMn can be controlled on the other hand. Y Fe X A Z The doping amount in the PO4 lattice is further selected when the number of carbon anchors of MOFs-derived carbon is similar to that of LiMn Y Fe X A Z When the molar mass content ratio of the phosphorus element of PO4 is 0.001-0.02, the obtained positive electrode material has higher conductivity and better stability, thereby being able to effectively improve the capacity, cycle performance and rate performance of the secondary battery prepared subsequently.
[0057] In a second aspect of the present application, the present application provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0058] (1) mixing the A source, the MOFs organic ligand and water to perform a first hydrothermal reaction to obtain an A-MOFs solution;
[0059] (2) mixing the metal B source, the COFs organic ligand and water to perform a second hydrothermal reaction to obtain a metal B-COFs solution;
[0060] (3) Add the phosphorus source aqueous solution to the lithium source aqueous solution and stir, then add the mixed aqueous solution of the iron source and manganese source and stir, then add the A-MOFs solution and heat to react, cool, filter and wash after the reaction is completed, and obtain LiMn Y Fe X A Z MOFs-derived carbon composite precursors of PO4;
[0061] (4) LiMn Y Fe X A Z The PO4 MOFs-derived carbon composite material precursor and the metal B-COFs are mixed and subjected to a third hydrothermal reaction, and after the reaction is completed, the mixture is cooled, filtered, washed, and dried to obtain a precursor powder;
[0062] (5) Calcine the precursor powder to obtain the positive electrode material.
[0063] The present application has found that, when the preparation method provided in the present application is adopted, the doping of A in A-MOFs between the crystal lattices of lithium manganese iron phosphate can be effectively achieved, thereby effectively reducing the Jaha-Teller effect of lithium manganese iron phosphate during the cycle process and inhibiting manganese dissolution; and, further selecting to introduce metal B-COFs in the precursor stage for coating and subsequent sintering can efficiently and stably prepare the positive electrode material, thereby improving the comprehensive performance of the secondary battery prepared subsequently.
[0064] In one embodiment, in step (1), the temperature of the first hydrothermal reaction is 185-225° C., and the time is 22-26 hours.
[0065] Exemplarily, the temperature of the first hydrothermal reaction can be any point value or any two points in the range between 185-225°C, such as 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, etc.; the time can be any point value or any two points in the range between 22-26h, such as 22h, 23h, 24h, 25h, 26h, etc.
[0066] The present application study found that when the temperature and time of the first hydrothermal reaction are selected within the above range, the synthesis effect of the obtained A-MOFs is better.
[0067] In one embodiment, in step (2), the temperature of the second hydrothermal reaction is 185-225° C., and the time is 22-26 hours.
[0068] Exemplarily, the temperature of the second hydrothermal reaction can be any point value or any two points in the range between 185-225°C, such as 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, etc.; the time can be any point value or any two points in the range between 22-26h, such as 22h, 23h, 24h, 25h, 26h, etc.
[0069] The present application study found that when the temperature and time of the second hydrothermal reaction are selected within the above range, the synthesis effect of the obtained metal-COFs is better.
[0070] In one embodiment, in step (3), the heating reaction temperature is 190-240° C. and the time is 13-17 hours.
[0071] Exemplarily, the temperature of the heating reaction can be any point value or any two points in the range of 190-240°C, for example, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, etc.; the time can be any point value or any two points in the range of 13-17h, for example, 13h, 14h, 15h, 16h, 17h, etc.
[0072] The present application study found that when the temperature and time of the heating reaction are selected within the above range, a more excellent doping effect can be achieved, thereby improving the conductivity and stability of the positive electrode material.
[0073] In one embodiment, in step (4), the temperature of the third hydrothermal reaction is 150-210° C., and the time is 22-26 hours.
[0074] Exemplarily, the temperature of the third hydrothermal reaction may be any point value or any two points in the range of 150-210°C, such as 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, etc.; the time may be any point value or any two points in the range of 22-26h, such as 22h, 23h, 24h, 25h, 26h, etc.
[0075] The present application has found that when the temperature and time of the third hydrothermal reaction are selected within the above range, a more excellent coating effect can be achieved, thereby improving the stability of the positive electrode material.
[0076] In one embodiment, in the step (5), the calcination temperature is 380-490° C. and the calcination time is 9-13 h.
[0077] Exemplarily, the calcination temperature can be any point value or any two point range value between 380-490°C, for example, 380°C, 385°C, 390°C, 395°C, 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, etc.; the time can be any point value or any two point range value between 9-13h, for example, 9h, 10h, 11h, 12h, 13h, etc.
[0078] In one embodiment, the COFs organic ligand includes at least one of terephthalaldehyde and 4',4-(benzothiadiazole-4,7-diyl)-dibenzaldehyde.
[0079] In one embodiment, the MOFs organic ligand includes at least one of terephthalic acid and isophthalic acid.
[0080] In one embodiment, based on the mass of the metal B-COFs, the mass percentage of the metal B is 6-10%.
[0081] For example, based on the mass of metal B-COFs, the mass percentage of metal B can be any point value or any two point range value between 6-10%, such as 6%, 7%, 8%, 9%, 10%, etc.
[0082] In one embodiment, the A source includes at least one of A oxide, A nitrate, and A hydroxide.
[0083] In one embodiment, the lithium source includes at least one of lithium hydroxide and lithium carbonate.
[0084] In one embodiment, the phosphorus source includes at least one of phosphoric acid and sodium phosphate.
[0085] In one embodiment, the iron source includes at least one of ferrous sulfate and its hydrate, and ferrous acetate.
[0086] In one embodiment, the manganese source includes at least one of manganese sulfate and its hydrate, and manganese carbonate.
[0087] In the third aspect of the present application, the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode active material layer includes the positive electrode material described in the present application.
[0088] In one embodiment, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.
[0089] The present application has no restrictions on the selection of the positive electrode conductive agent, and the positive electrode conductive agent conventionally used in the art can be selected, such as at least one of SuperP, carbon nanotubes, and graphene.
[0090] The present application has no restrictions on the selection of positive electrode binders, and positive electrode binders conventionally used in the art may be selected, such as at least one of PVDF, PTFE, PAANa, CMC, SBR, and sodium alginate.
[0091] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder.
[0092] The present application has no restrictions on the selection of negative electrode active materials, and negative electrode active materials commonly used in the art may be selected, such as at least one of graphite and silicon-doped graphite.
[0093] The present application has no restrictions on the selection of the negative electrode conductive agent, and the negative electrode conductive agent conventionally used in the art can be selected, such as at least one of CNT, acetylene black, and Ketjen black.
[0094] The present application has no restrictions on the selection of negative electrode binders, and negative electrode binders conventionally used in the art may be selected, such as at least one of PVDF, PTFE, PAANa, CMC, SBR, and sodium alginate.
[0095] The present application has no limitation on the diaphragm, and the diaphragm conventionally used in the art can be selected; illustratively, the material of the diaphragm can be polypropylene, polyethylene, or a composite of polypropylene and polyethylene, etc.
[0096] In a fourth aspect of the present application, the present application provides an electrical device, comprising the secondary battery described in the present application.
[0097] Example 1
[0098] The present invention provides a positive electrode material and a secondary battery. The preparation method of the positive electrode material and the secondary battery comprises the following steps:
[0099] (1) Preparation of positive electrode materials
[0100] S1. Add Zr(NO3)4·3H2O, terephthalic acid and deionized water in a certain molar ratio into a 200 mL hydrothermal reactor and react at 190°C for 24 h to obtain a Zr-MOFs solution;
[0101] S2, adding a mixed solution of cobalt acetate, 4',4-(benzothiadiazole-4,7-diyl)-dibenzaldehyde, n-butanol, o-dichlorobenzene and acetic acid (the mass ratio of n-butanol, o-dichlorobenzene and acetic acid is 1:1:1) into a 200mL hydrothermal reactor at a certain molar ratio, and reacting at 140°C for 48h to obtain a Co-COFs solution;
[0102] S3, LiOH·H2O and H3PO4 were dissolved in 30mL and 20mL of water respectively, and then the H3PO4 aqueous solution was added dropwise to the LiOH·H2O aqueous solution through a constant pressure funnel, accompanied by sufficient magnetic stirring to form a white suspension, which was recorded as solution 1. Then FeSO4·7H2O and MnSO4·H2O were dissolved in 20mL of water, which was recorded as solution 2. Solution 2 was added dropwise to solution 1, and after sufficient stirring, it was transferred to the reactor with Zr-MOFs solution and reacted at 210℃ for 15h. After the reaction was completed, it was cooled to room temperature, and the product was washed with deionized water 3 times and dried to obtain LiMnY Fe X A Z MOFs-derived carbon composite precursors of PO4;
[0103] S4, LiMn Y Fe X A Z The MOFs-derived carbon composite precursor of PO4 was added to a 200 mL hydrothermal reactor, and the Co-COFs solution was added to the hydrothermal reactor at a certain molar ratio, and reacted at 170°C for 24 hours. After the reaction was completed, it was cooled to room temperature, the product was washed with deionized water three times, and dried at 110°C for 10 hours to obtain the precursor powder;
[0104] S5. Calcine the precursor powder at 450° C. for 11 h in an Ar environment to obtain a positive electrode material.
[0105] (2) Preparation of positive electrode sheet
[0106] The positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) obtained in the experiment were fully stirred in a N-methyl methyl pyrrolidone solvent system at a mass ratio of 80.5:13.0:6.5. After being stirred evenly, a positive electrode slurry was obtained, and the slurry was coated on a composite primer Al foil with carbon coating (purchased by myself), baked, rolled, and slit to obtain a positive electrode sheet.
[0107] (3) Preparation of negative electrode sheet
[0108] Graphite, conductive agent carbon nanotubes, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose were stirred and mixed in deionized water at a mass ratio of 96.2:1.8:0.9:1.1. After being mixed evenly, the negative electrode slurry was coated on Cu foil, baked, rolled, and cut into strips to obtain a negative electrode sheet.
[0109] (4) Preparation of electrolyte
[0110] The organic solvents are uniformly mixed according to the mass ratio to obtain an organic solvent mixture, the detailed mass ratio is: vinyl ester (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 23:14:5:27:31. Lithium salt LiPF6 is added to the organic solution, and the mass ratio of the added mass to the organic solvent is 9.5:90.5. The final solution obtained after uniform mixing is the electrolyte of the lithium ion battery.
[0111] (5) Preparation of secondary batteries
[0112] Stack the positive electrode sheet, separator, and negative electrode sheet in order, and wind them to obtain an electrode assembly. When folding the electrode sheet, make sure that the separator completely separates the positive and negative electrode sheets. Place the motor assembly in a packaging shell, inject electrolyte into the packaging shell and package it, and finally obtain a lithium-ion battery.
[0113] Embodiment 2-4
[0114] The embodiment of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of embodiment 1 is that the amount of raw material added to the core layer is adjusted to achieve the parameters in Table 1.
[0115] Embodiment 5-6
[0116] The embodiment of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of embodiment 1 is that the amount of the shell layer added is adjusted to achieve the parameters in Table 1.
[0117] Embodiment 7-8
[0118] The embodiment of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that the synthesis of the metal-COFs is adjusted to achieve the parameters in Table 1.
[0119] Examples 9-10
[0120] The embodiment of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that the synthesis of A-MOFs is adjusted to achieve the parameters in Table 1.
[0121] Examples 11-12
[0122] The embodiment of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that the synthesis of the metal-COFs is adjusted to achieve the parameters in Table 1.
[0123] Comparative Example 1-2
[0124] The comparative example of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that the amount of the shell layer added is adjusted to achieve the parameters in Table 1.
[0125] Comparative Example 3
[0126] The comparative example of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that A-MOFs are not doped.
[0127] Comparative Example 4
[0128] The comparative example of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that metal-COFs coating is not performed.
[0129] Comparative Example 5
[0130] The comparative example of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that the doping of A-MOFs and the coating of metal-COFs are not performed.
[0131] Comparative Example 6
[0132] The comparative example of the present application provides a positive electrode material and a secondary battery. The difference between the preparation method of the positive electrode material and the secondary battery and that of Example 1 is that conventional carbon (glucose) is used for coating.
[0133] The structural formula of the core layer in the positive electrode materials prepared in Examples 1-12 and Comparative Examples 1-6, the molar ratio m of the core layer and the shell layer, the type of metal in the metal B-doped COFs-derived carbon, the number of carbon-carbon double bonds in the smallest monomer molecule in the metal B-doped COFs-derived carbon n, the number of carbon anchor points in the MOFs-derived carbon and LiMn Y Fe X A Z The ratio of the molar mass content of phosphorus element in PO4 l and the mass percentage of metal based on the mass of metal B-COFs o are shown in Table 1;
[0134] Table 1
[0135]
[0136]
[0137] The performance tests of the positive electrode materials and secondary batteries prepared in the examples and comparative examples include the following aspects:
[0138] 1. Conductivity test of positive electrode materials: Use the Ohm method to test. First, put the sample powder into the test module and compact it. Then measure the height (recorded as L) and diameter (recorded as D) of the compacted module. Then use a multimeter to test the module resistance (recorded as R). The powder conductivity G of the sample can be calculated;
[0139] 2. Gram capacity test: Take 6 samples of each secondary battery and charge them to 4.30V at room temperature at a constant current and constant voltage condition at a rate of 0.33C, with a cut-off current of 0.02C. Then, discharge them at a constant current at a rate of 0.33C until the voltage is cut off at 2.5V. Record the obtained capacity, and divide the obtained capacity by the mass of the active material of the positive electrode material to obtain the gram capacity of the positive electrode material;
[0140] 3. Cycle performance test: Take 6 samples of each secondary battery and test its cycle performance at 45°C. The cycle steps are to repeatedly charge and discharge the secondary battery, calculate the cycle capacity retention rate of the secondary battery, and when the capacity retention rate of the secondary battery is lower than 70%, the cycle test ends and the number of cycles is recorded;
[0141] The detailed steps are: charge to 4.30V at 0.5C constant current and constant voltage, the cut-off current is 0.02C, and discharge to 2.5V at 1.0C constant current. This first charge and discharge process is one cycle. Repeat this cycle step until the capacity retention rate of the lithium-ion battery is less than 70%. The cycle test is completed and the cycle number of the lithium-ion battery is recorded.
[0142] 4. Rate performance test: Take 6 samples of each secondary battery, charge to 4.30V under constant current and constant voltage conditions at a rate of 0.5C, and the cut-off current is 0.02C. Then, discharge at a constant current at a rate of 0.33C until the voltage is cut off at 2.5V. The discharge capacity at this step is S1. Charge to 4.30V under constant current and constant voltage conditions at a rate of 0.5C. The cut-off current is 0.02C. Then, discharge at a constant current at a rate of 5.0C until the voltage is cut off at 2.5V. The discharge capacity at this step is S2. The discharge capacity percentage obtained by S2 / S1*100% is the rate performance test result;
[0143] The results obtained are shown in Table 2;
[0144] Table 2
[0145]
[0146] It can be seen from Table 2 that when the technical solution provided by the present application is adopted, the conductivity of the obtained positive electrode material is relatively high, at 29×10 -4 S / cm or more, the obtained secondary battery has a higher capacity, excellent cycle performance and rate performance; specifically, the gram capacity of the obtained secondary battery is above 146 mAh / g, the number of cycles is above 510 cls, and the percentage of reaction rate performance is above 84%;
[0147] It can be seen from Examples 1-12 and Comparative Examples 1-2 that when the molar ratio of the core layer and the shell layer of the positive electrode material is not within the range given in the present application, the conductivity of the obtained secondary battery decreases significantly, and the gram capacity and rate performance also show a certain downward trend; it can be seen from Examples 1-12 and Comparative Example 3 that when A-MOFs doping is not performed, the conductivity of the obtained secondary battery decreases significantly, and the cycle performance and rate performance also show a significant downward trend; it can be seen from Examples 1-12 and Comparative Example 4 that when metal B-COFs coating is not performed, the conductivity of the obtained secondary battery decreases significantly, and the cycle performance and rate performance also show a significant downward trend; it can be seen from Examples 1-12 and Comparative Example 5 that when neither A-MOFs doping nor metal B-COFs coating is performed, the conductivity of the obtained secondary battery decreases sharply, and the gram capacity of the secondary battery also decreases significantly, and the cycle performance and rate performance also decrease significantly; it can be seen from Examples 1-12 and Comparative Example 6 that when conventional carbon coating is used, the comprehensive performance of the obtained secondary battery also decreases significantly.
[0148] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material is a core-shell structure, and the core layer includes LiMn Y Fe X A Z A MOFs-derived carbon composite material of PO4, wherein the shell layer comprises metal B-doped COFs-derived carbon; LiMn Y Fe X A Z in A PO4, 0 < X < 1, 0 < Y < 1, 0.001 ≤ Z / (X + Y) ≤ 0.005, and X + Y + Z = 1; A is selected from at least one of Ni, Al, Fe, Mg, Cu, Ti, W, La, Zr, Nb, Pd, Co, Ni, Mn, Zn, and Ta; In the metal B-doped COFs-derived carbon, the metal B includes at least one of Co, La, Ti, Zr, and Sc; The molar ratio of the core layer to the shell layer is 1:(0.001-0.005).
2. The positive electrode material according to claim 1, characterized in that In the metal B-doped COFs-derived carbon, the number of carbon-carbon double bonds in the smallest monomer molecule is ≥2.
3. The positive electrode material according to claim 1, characterized in that The LiMn Y Fe X A Z The number of carbon anchor points of MOFs-derived carbon in MOFs-derived carbon composites of PO4 is similar to that of LiMn Y Fe X A Z The molar mass content ratio of phosphorus element in PO4 is 0.001-0.
02.
4. The method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing the A source, the MOFs organic ligand and water to perform a first hydrothermal reaction to obtain an A-MOFs solution; (2) mixing the metal B source, the COFs organic ligand and water to perform a second hydrothermal reaction to obtain a metal B-COFs solution; (3) Add the phosphorus source aqueous solution to the lithium source aqueous solution and stir, then add the mixed aqueous solution of the iron source and manganese source and stir, then add the A-MOFs solution and heat to react, cool, filter and wash after the reaction is completed, and obtain LiMn Y Fe X A Z MOFs-derived carbon composite precursors of PO4; (4) LiMn Y Fe X A Z The PO4 MOFs-derived carbon composite material precursor and the metal B-COFs are mixed and subjected to a third hydrothermal reaction, and after the reaction is completed, the mixture is cooled, filtered, washed, and dried to obtain a precursor powder; (5) Calcine the precursor powder to obtain the positive electrode material.
5. The preparation method according to claim 4, characterized in that: In the step (1), the temperature of the first hydrothermal reaction is 185-225° C. and the time is 22-26 hours; And / or, in step (2), the temperature of the second hydrothermal reaction is 185-225° C. and the time is 22-26 h; And / or, in step (3), the heating reaction temperature is 190-240° C. and the time is 13-17 h; And / or, in step (4), the temperature of the third hydrothermal reaction is 150-210° C. and the time is 22-26 h; And / or, in the step (4), the calcination temperature is 380-490° C. and the calcination time is 9-13 h.
6. The preparation method according to claim 4, characterized in that: The COFs organic ligand includes at least one of terephthalaldehyde and 4',4-(benzothiadiazole-4,7-diyl)-dibenzaldehyde; And / or, the MOFs organic ligand includes at least one of terephthalic acid and isophthalic acid.
7. The preparation method according to claim 4, characterized in that: Based on the mass of metal B-COFs, the mass percentage of metal B is 6-10%.
8. The preparation method according to claim 4, characterized in that: The A source includes at least one of an oxide of A, a nitrate of A, and a hydroxide of A; And / or, the lithium source includes at least one of lithium hydroxide and lithium carbonate; And / or, the phosphorus source includes at least one of phosphoric acid and sodium phosphate; And / or, the iron source includes at least one of ferrous sulfate and its hydrate, and ferrous acetate; And / or, the manganese source includes at least one of manganese sulfate and its hydrate, and manganese carbonate.
9. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the positive electrode material as claimed in any one of claims 1 to 3.
10. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Preparation method and product of nitrogen-doped carbon material, negative plate and secondary battery
CN114520325A
Preparation method and application of covalent organic framework-carbon coated positive electrode material
CN115724417A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN117199350A
Coating material of lithium ion battery positive electrode material as well as preparation method and application of coating material
CN117229525A
COF composite polymer solid electrolyte and preparation and application thereof
CN118263510A